(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Congenital heart disease (CHD) remains a significant cause of morbidity and mortality in infants worldwide. While genetic factors contribute substantially to the etiology of CHD, there is increasing recognition of the role played by non-genetic risk factors. Understanding these modifiable factors is crucial for prevention, early intervention, and improving overall outcomes for affected individuals. This review synthesizes current knowledge on non-genetic risk factors associated with the development of CHD. By identifying these factors, healthcare providers can implement targeted interventions and public health strategies to reduce the incidence and severity of CHD. A comprehensive literature search was conducted, encompassing studies published in peer-reviewed journals, epidemiological reports, and meta-analyses. Data were systematically extracted and analyzed to identify non-genetic risk factors associated with CHD. Emphasis was placed on maternal factors, environmental exposures, and lifestyle-related variables. Non-genetic risk factors significantly influence the incidence of congenital heart disease. This review emphasizes the importance of identifying and addressing modifiable factors to reduce the burden of CHD. Public health initiatives aimed at promoting maternal health, discouraging harmful lifestyle choices, and raising awareness about teratogenic exposures are pivotal. By focusing on these non-genetic risk factors, healthcare systems can move toward a multifaceted approach that combines genetic screening, risk factor modification, and early intervention, thereby potentially reducing the prevalence of congenital heart disease and improving the overall health outcomes for affected individuals.